Pendampingan Guru SDI Ibnu Miskawaih dalam Pemanfaatan Storybird: Media Digital Storytelling untuk Menumbuhkan Minat Baca Siswa melalui Cerita Bergambar Interaktif - Putri, Willa; Aisah, Siti; Sari, Siti Novita (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The use of digital storytelling media is considered an effective way to increase students’ reading interest. This community service program was conducted from April 2 to June 2, 2025, to assist teachers at SDI Ibnu Miskawaih in utilising Storybird as a digital storytelling medium to create more engaging and creative literacy learning experiences. The program also aimed to enhance teachers’ digital literacy, as evidenced by the consistent integration of technology into the learning process. The method applied was Participatory Action Research (PAR), which consisted of five stages: planning, implementation, classroom application, evaluation and reflection, and reinforcement, as well as the dissemination of results. The activities began with identifying teachers’ initial knowledge, followed by technical training and hands-on practice in creating digital stories. The results indicate a significant improvement in teachers’ understanding and skills in using Storybird. Teachers were able to integrate this medium into lesson plans (RPP) and demonstrated high enthusiasm during the training sessions. Challenges such as limited devices and low digital literacy were successfully addressed through interactive and collaborative approaches. Storybird has been proven to foster students’ creativity, increase their reading interest, and strengthen collaboration between teachers, students, and parents.